Analysis of agreement between 4 lactate threshold measurements methods in professional soccer players - Cerda-Kohler, H.; Burgos-Jara, C.; Ramirez-Campillo, R.; Valdés-Cerda, B.; Báez, E.; Zapata-Gómez, D.; Cristóbal Andrade, D.; Izquierdo, M. (The Journal of Strength and Conditioning Research, 2016)
Lactate threshold (LT) represents the inflection point of blood lactate values from rest to high-intensity exercise during an incremental test, is commonly used to determine exercise intensity, and is related to different positional roles of elite soccer players. Different methodologies have been adopted to determine the LT; however, the agreement between these methodologies in professional soccer players is unclear. Seventeen professional soccer players were recruited (age 24.7 ± 3.7 years, body mass 70.1 ± 5.3 kg, height 172.8 ± 7.3 cm) and performed an incremental treadmill test until volitional fatigue. Speed at LT (LTspeed), heart rate at LT (LTHR), and lactate values from capillary blood samples obtained at 3-minute intervals were analyzed using 4 LT measurement methods: visual inspection (VI), maximum distance (Dmax), modified Dmax (DmaxM), and logarithmic (log-log). Only Bland-Altman analysis for LTHR showed agreement between VI and Dmax, between VI and DmaxM, and between Dmax and DmaxM methods. No agreement between methods was observed after intraclass correlation coefficient and 95% one-sided lower-limit analysis. Comparative results showed that LTspeed was lower (p < 0.01) with the log-log method compared with the Dmax method and lower (p < 0.01) with the latter compared with the VI and DmaxM methods. Regarding LTHR, higher (p < 0.01) values were observed using the VI, DmaxM, and Dmax methods compared with the log-log method. Therefore, VI, Dmax, DmaxM, and log-log methods should not be used interchangeably for LT measurement. More studies are needed to determine a gold standard for LT detection in professional soccer players.